Mild dehydration impaired intermittent sprint performance and thermoregulation in females - Driscoll, R. L.; McCarthy, D. G.; Palmer, M. S.; Spriet, L. L. (Applied Physiology, Nutrition, and Metabolism, 2020)
The effects of mild dehydration during ice hockey are well-studied in males but not females. In a randomized, crossover design, 11 female varsity hockey players drank no fluid (1.7% ± 0.3% body mass loss) or water to maintain hydration during simulated-hockey exercise. Core temperature (P < 0.01) and perceived fatigue (P = 0.02) were higher and sprint power lower (P < 0.01) when mildly dehydrated. Thus, mild dehydration may impair hockey performance and thermoregulation while increasing perceived fatigue in females.